Overcoming Disruption in Special Collections Public Services. Issue 1 (3rd January 2022) - Planton, Isabel; Ferrara, Amanda
Abstract: Special collections and archives workers have unique experiences in providing service to their patron base while also working to overcome disruption and physical displacement. The disruption may take the form of a major renovation, a closure due to natural disaster, being forced out of a library space, budget cuts, or other operational issues. This article captures the experiences of twenty-eight staff members providing access services to their subset of users, in the form of interviews, in order to reflect upon how our profession connects with, provides services to, and places value on the relationships we cultivate with the public. We sought to gain insight from those who have experienced disruptions to their services in the past in order to apply this knowledge to the pandemic situation of 2020 and 2021, as well as those experiencing major disruptions in the future. The interview responses are a general representation of what staff may endure when embarking on a project that is a major disruption to service delivery. The experiences of the participants revealed a cyclical interconnectedness between the themes, indicating the complex nature of work involving human beings. The responses provide tangible recommendations to those planning for, beginning, or experiencing a disruption.